Auxetic mechanical metamaterial based stretchable electronics - Jiang, Ying (Nanyang Technological University, 2020)
Stretchable electronics have attracted tremendous attention in recent years, driven by the high demands of human-machine interfaces including wearable healthcare platform, implantable bioelectronics, soft robotics and so on. Compared to conventional silicon-based, rigid electronics, such stretchable electronics with similar mechanical properties to the soft, stretchable and curvilinear biological tissues reduced the mechanical mismatch, elevating signal fidelity in healthcare signal monitoring. Among stretchable electronics, stretchable strain sensors and stretchable electrodes are the most vital components, where the former transduce mechanical stimuli into readable electrical signals, and the latter electrically connects components and detect electrophysiological indicators. However, there is still big challenges to achieve high sensitivity, stretchability, cyclic durability, conformality via simple fabrication procedures in stretchable strain sensors and electrodes. Here a conceptually novel strategy is proposed to solve such challenges: Auxetic mechanical metamaterial employment. The design principle is that, the electrical performance of stretchable electronics is determined via the microscopic morphology of active layer, where can be regulated via mechanical design and the resulting strain distribution. Therefore, it is hypothesized that auxetic mechanical metamaterials with unique, extraordinary mechanical properties can rationally regulate heterogeneous strain distribution in stretchable electronics, thus achieving high electrical and mechanical performance under applied strain. In detail, the strategy of auxetic mechanical metamaterial was firstly employed in stretchable strain sensors. For conventional flat film-based strain sensors, the transverse Poisson’s compression counteracts the longitudinal stretching, leads to intrinsic inadequate sensitivity for practical application. Here the auxetic metamaterials with bi-axial expansion trend are incorporated into stretchable strain sensors, largely enhancing the gauge factor from ~24 to ~835 as a 24-fold improvement. The stretchability of such auxetic strain sensors can reach ~100% with good cyclic durability of >2,000 cycles. As a proof of concept, human radial pulse wave was detected with high signal-to-noise ratio and abundant medical details, experimentally proving the effectiveness of this strategy. Next, theoretical models are established to investigate the underlying mechanism in between experimental phenomenon for auxetic metamaterial strain sensors. Finite element analysis was employed to investigate the strain distribution and microcrack length in presence of auxetic structures. Voltage drop model explains why such elongated microcracks enhance the sensitivity, consistent with experimental results. To wrap the whole process, an overall model based on elongated microcracks and heterogeneous strain distribution was established for complete theoretical system, beneficial for scientific foundation as well as practical device optimization. Furthermore, three-dimensional auxetic foam was employed to fabricate high performance stretchable electrodes with both electrical and mechanical stretchability. Such auxetic polyurethane foam via simple, thermal-compression fabrication process exhibits tri-axial negative structural Poisson’s ratio of -0.3 at 40% strain, leading to expansion in thickness directions upon longitudinal stretching. Such auxeticity can be rationally tuned via fabrication parameters, and elevates both mechanical (150% to 190%) and electrical stretchability (20% to 150%). The above results show that the strategy of employing auxetic metamaterials is effective to fabricate high performance stretchable strain sensors and stretchable electrodes, which can be further utilized for other stretchable electronics. This pioneering work brings the whole mechanical metamaterial field into the view of stretchable electronics. The functionalities of stretchable electronics are heavily dependent on mechanical properties under deformation, thus metamaterials with superior mechanical behaviors could inject vitality and build momentum to this field.